Investigating the impact of the number of COVID-19 reinfections, vaccination status, risk factors, and reinfection interval on long COVID symptomatology - Björn Nicolay; Raquel Gómez Bravo; Djenna Hutmacher; Charles Benoy; Claus Vögele (Discover Public Health)
Abstract Despite the acknowledged global importance of long COVID (LC), several underlying mechanisms of this chronic illness are still far from being fully understood. Therefore, the present study evaluated the roles of the number of COVID-19 reinfections, vaccination status, pre-existing risk factors, and reinfection interval on illness symptomatology at each respective COVID-19 reinfection as well as on experienced LC symptoms in a sample of N = 552 LC patients. We employed a cross-sectional online survey. Data from n = 214 LC patients having experienced between one and three COVID-19 reinfections were included in the final analyses. Results indicated that patients with more COVID-19 reinfections experienced a higher number of LC symptoms. Furthermore, vaccinated patients and patients without risk factors reported fewer LC symptoms than their respective counterparts. Additionally, vaccination might serve as a long-term buffer for developing anxiety and/or depression, and patients with a risk factor and repeated COVID-19 infections over a longer time interval more frequently reported “other ear, nose, and throat disorder” symptoms. Overall, the outcomes further underline the heterogenous nature of LC, while providing several noteworthy indications for the individual and joint contributions of several empirically validated factors for LC symptomatology.